Drug abuse and the law / Ramonah Ramthan - Ramthan, Ramonah (Faculty of Law, 1987)
The history of drug abuse starts since the end of 19th. century when the Chinese and Indians immigrants came to our country and brought along the habit of opium and ganja smoking. During those days, opium and ganja smoking was not an offence since it was not only as a means of relaxation but as remedy for various sickness especially among the old people. However the following years showed an increase in the undiscriminately use of dangerous drugs, The number of identified drug addicts in our country now is 500,000 and recognising that drug addiction and trafficking have been increasing at an alarming rate, the Honourable Prime Minister, Datuk Seri Dr. Mahathir Mohamad when launching the anti-drug camoaign on February 19, 1983 has declared it as the country's number one enemy. Being the country's number one enemy, the Government has placed drug problem at the highest level of priority by declaricing it a primary security concern and to be treated as a major threat to the national security.